2002
DOI: 10.1128/jcm.40.1.80-83.2002
|View full text |Cite
|
Sign up to set email alerts
|

Immunochromatographic Strip Test for Rapid Detection of Diphtheria Toxin: Description and Multicenter Evaluation in Areas of Low and High Prevalence of Diphtheria

Abstract: An immunochromatographic strip (ICS) test was developed for the detection of diphtheria toxin by using an equine polyclonal antibody as the capture antibody and colloidal gold-labeled monoclonal antibodies specific for fragment A of the diphtheria toxin molecule as the detection antibody. The ICS test has been fully optimized for the detection of toxin from bacterial cultures; the limit of detection was approximately 0.5 ng of diphtheria toxin per ml within 10 min. In a comparative study with 915 pure clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 12 publications
0
23
0
Order By: Relevance
“…Classical tests commonly used to demonstrate the toxigenicity of a C. diphtheriae strain (Elek and IDR test) give a delayed answer to the diagnosis (usually more than 48 h) and are time-consuming to set up. A rapid immunochromatographic (ICS) method for detection of diphtheria toxin has recently been developed (Engler et al 2002). During epidemics, field studies within the former USSR showed 99% correlation between the Elek and ICS test (Koslov et al 2000).…”
Section: Laboratory Diagnosismentioning
confidence: 99%
“…Classical tests commonly used to demonstrate the toxigenicity of a C. diphtheriae strain (Elek and IDR test) give a delayed answer to the diagnosis (usually more than 48 h) and are time-consuming to set up. A rapid immunochromatographic (ICS) method for detection of diphtheria toxin has recently been developed (Engler et al 2002). During epidemics, field studies within the former USSR showed 99% correlation between the Elek and ICS test (Koslov et al 2000).…”
Section: Laboratory Diagnosismentioning
confidence: 99%
“…Similar IC tests, such as those for diphtheria toxin (31) and Plasmodium falciparum HRP-2 antigen (11), have greater sensitivities. Our IC test may have a lower sensitivity due to its dependence upon the extraction of an OMP.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the transmission of HIV could potentially be decreased if chancroid were eliminated (1). IC tests have been developed for other bacterial antigens (11,31) and have a number of advantages over conventional microbiological techniques, including ease of performance, stability in temperate climates, and comparatively low cost, among many others. In the case of H. ducreyi, the greatest advantage would be the rapidity of diagnosis of the etiology of the genital ulcer.…”
Section: Discussionmentioning
confidence: 99%
“…a dipstick assay was developed for the rapid phenotypic detection of diphtheria toxin in clinical isolates [37]. This assay does not rely on polyclonal DAT, but instead incorporates a colloidal gold-coupled mAb specific for the toxin molecule [37], while other similar assays make use of alkaline phosphatase-coupled or fluorescein isothiocyanatecoupled mAbs [38,39].…”
Section: Alternatives For Diphtheria Antitoxin For Diagnosticsmentioning
confidence: 99%